2015
DOI: 10.1002/2015wr017199
|View full text |Cite
|
Sign up to set email alerts
|

Are all runoff processes the same? Numerical experiments comparing a Darcy‐Richards solver to an overland flow‐based approach for subsurface storm runoff simulation

Abstract: Hillslope runoff theory is based largely on the differentiation between infiltration excess overland flow, saturation excess overland flow, and subsurface stormflow. Here we explore to what extent a 2-D friction-based overland flow model is useful for predicting hillslope-scale subsurface stormflow, posited here as phenomenologically the same as infiltration excess at depth. We compare our results to a 3-D variably saturated Darcy-Richards subsurface solver for individual rainfall runoff events. We use field d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 67 publications
(102 reference statements)
2
37
0
Order By: Relevance
“…This reflects a system type similar to the theory proposed by Berghuijs and Kirchner () where groundwater can be much older than the streamflow when most of the streamflow originates from the highly conductive soil layer above the bedrock groundwater which produces subsurface stormflow (cf. Ameli et al, ). Such an interpretation is supported by the recent work of Gabrielli ().…”
Section: Discussionmentioning
confidence: 99%
“…This reflects a system type similar to the theory proposed by Berghuijs and Kirchner () where groundwater can be much older than the streamflow when most of the streamflow originates from the highly conductive soil layer above the bedrock groundwater which produces subsurface stormflow (cf. Ameli et al, ). Such an interpretation is supported by the recent work of Gabrielli ().…”
Section: Discussionmentioning
confidence: 99%
“…Ameli et al. ). In the groundwater–surface water interaction model, the water level at each intact wetland was considered to be equal to the median of the long‐term water level in the wetland simulated using the surface flow routing model during the eight‐month study period; this water level was then used as the constant head boundary condition at the intact wetland.…”
Section: Hydrologic Modelmentioning
confidence: 99%
“…In addition, given the small rainfall to evapotranspiration ratio in the Nose Creek watershed, typical of a dry continental climate, there is a small likelihood of the occurrence of lateral water movement in the shallow unsaturated zone through subsurface stormflow, which is typically observed in humid forested landscapes with permeable soils and a relatively large rainfall to evapotranspiration ratio (c.f. Ameli et al 2015). In the groundwater-surface water interaction model, the water level at each intact wetland was considered to be equal to the JAWRA JOURNAL OF THE AMERICAN WATER RESOURCES ASSOCIATION median of the long-term water level in the wetland simulated using the surface flow routing model during the eight-month study period; this water level was then used as the constant head boundary condition at the intact wetland.…”
Section: Groundwater-surface Water Interaction Modelmentioning
confidence: 99%
“…Downer and Ogden [] found that “effective” parameters could be used to overcome this effect, but these changes in the parameter values resulted in too much infiltration as the soil surface approached saturation. Two and three‐dimensional Richards' equation simulations of even small catchments at appropriate spatial resolutions require very long run times [ Ameli et al ., ], when the solution domain is required to meet the REV assumption.…”
Section: Introductionmentioning
confidence: 99%